Lexical-semantic Features of Anthroponyms in English Language - JURAEVA, IRODA AKHMEDOVNA (The journal of contemporary issues in business and government, 2021)
This article discusses the use of English anthroponyms in the social sphere, anthroponymic formulas, signals of anthroponyms. It also discusses some of the research that has emerged as a result of a comparative analysis of the etymology of anthroponyms with Russian and other languages. The nominative value of names, anthroponymic formulas, and signals of anthroponyms are also discussed.